MANAGEMENT STYLES IN A GLOBAL MARKET ECONOMY - Luchien Karsten (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
Globalization is the intensification of the spatial organization ofsocial relations and transactions, which put distant localities and local activities at a level of worldwide range, consequence and significance. These activities cluster into new reality like a globally operating market system and a globally developing technoscience. The question is to what extent a global civil society will come about too. At the level of internationally operating firms management styles will have to be developed to enhance the understanding of cultural heterogeneity within this global civil society. Cultural complexity will increase due to the intensification of interactions and transactions. Within and between internationally operating firms. Communicative rationality in terms of dialogue and conversations should be reinforced to deal adequately with this complexity. Communicative rationality perceives language not only as a mere representation of an objective reality but also as a human practice in a social context. Firms operating as communities of practice will enhance through proper management styles the reciprocal understanding we need in a world economy.